2014
DOI: 10.1007/s13361-014-0844-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct Analysis of Triacylglycerols from Crude Lipid Mixtures by Gold Nanoparticle-Assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: Triacylglycerols (TAGs), essential energy storage lipids, are easily detected by conventional MALDI MS when occurring on their own. However, their signals are easily overwhelmed by other lipids, mainly phosphatidylcholines (PCs) and, therefore, require purification. In order to profile TAGs from crude lipid mixtures without prefractionation, we investigated alternative matrixes that can suppress phospholipid ion signals and enhance cationization of TAGs. We found that an aqueous solution of citrate-capped gold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Other lipids (e.g., phospholipids, sphingomyelin, fatty acids, etc.) also consistently formed silver‐analyte adducts, and some species further fragmented in experiments by Muller et al Sputtered gold has been utilized for ionization of cholesterol, but this is only the second report of in solution AuNP sample preparation, giving an opportunity to further probe fundamental ionization effects . It has now been shown that 20‐nm AgNPs, 2‐nm AuNPs, and 5‐nm AuNPs effectively ionize cholesterol.…”
Section: Resultsmentioning
confidence: 99%
“…Other lipids (e.g., phospholipids, sphingomyelin, fatty acids, etc.) also consistently formed silver‐analyte adducts, and some species further fragmented in experiments by Muller et al Sputtered gold has been utilized for ionization of cholesterol, but this is only the second report of in solution AuNP sample preparation, giving an opportunity to further probe fundamental ionization effects . It has now been shown that 20‐nm AgNPs, 2‐nm AuNPs, and 5‐nm AuNPs effectively ionize cholesterol.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid assignment for mass peaks obtained by NP-LDI, MALDI, and high-energy Ar cluster SIMS in the mouse brain in positive ion mode (Table 1) and peak assignments for NP-LDI and Ar GCIB SIMS spectra in negative ion mode (Table 2) [26, 40, 48, 66]. The peaks that appear in each MSI technique are weighted by (+).…”
Section: Resultsmentioning
confidence: 99%
“…Another positive effect is that the spatial resolution depends only by instrumental specification like laser spot diameter and not by the crystallization of the matrix16. Metallic NPs have been largely employed in MALDI experiments1718192021 and in particular, TiO2 nanoparticles have been used for distribution studies of small endogenous molecules2223.…”
mentioning
confidence: 99%